Perspectives on Development (Part 2) - Tolosa, Benjamin T, Jr (Archīum Ateneo, 2020)
In this two-part lecture, Dr. Tolosa shares perspectives which have emerged from the field of development studies and development economics. Speaker: Dr. Tolosa is a Professor of Political Science and Associate Dean for the Core Curriculum, Loyola Schools, Ateneo de Manila University. He also teaches in the Department of Economics and the Development Studies Program of which he was the founding Director. He received his A.B. in Economics (Honors Program) magna cum laude from the Ateneo de Manila University, his M.A. in Development Studies from the University of East Anglia as a British Council scholar, and his Ph.D. in Political Science from the University of Minnesota as a Fulbright-MacArthur scholar. His scholarly research and public intellectual work are deeply connected with his teaching and university/community service. His academic interests are in the fields of Politics and Development; Global Political Economy and Governance; Comparative Ideologies; Generations and Social Change; Religion, Social Formation, and Democratization. They inform his work in youth sociopolitical education and leadership formation. His teaching and research are inspired by his engagement with student organizations, Church-based groups, and civil society movements. He hopes these reflections support the building of democratic institutions by helping create both intellectual frames for sociopolitical analysis and concrete options for political engagement.